Pathophysiology of Rabies Encephalitis and Treatment of Rabies : A Literature Review - Ginuluh, Gintis Dhimar; Kamila, Alya Syafa; Humam, Anang Muh Naufal; Helmiana, Putri Fatimah; Pratiwi, Rukmanggana Satya; Hunaifi, Ilsa; Arsy, Lazuardi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Rabies is a zoonotic disease transmitted by the saliva of mammals infected with Rabies lyssavirus. Rabies is a lethal disease that is still a health problem in Indonesia. This article aims to review the clinical features, diagnosis, pathophysiology, and management of rabies. This research collects and analyzes literature related to rabies that was conducted through Google Scholar, Pubmed, and ScienceDirect. The review results show that rabies with clinical features, especially rabies encephalitis had poor outcomes. Rabies is a neurotropic virus that spreads through neurons and attack CNS causing rabies encephalitis. The management is categorized into pre-exposure treatment, post-exposure treatment, and palliative treatment. An understandable information regarding the mechanism of rabies encephalitis and rabies management is very important to minimize deaths caused by rabies.